Sustainability in the wine industry: Key questions and research trends a - Cristina Santini; Alessio Cavicchi; Leonardo Casini (Agricultural and Food Economics, 2013)
Sustainability is playing a key role in the wine industry as shown by the attention paid at several levels by the academia, institutions and associations. Nevertheless, the principle itself of sustainability opens a wide debate and it significantly affects firms in all their activities. Using a systematic literature review, this paper wants to highlight some of the questions that academics must face when they approach the issue of sustainability with a specific focus on the wine industry. In particular the paper aims to: highlight where research is going and what has already been done; define the contribution of background research in explaining the determinants of sustainable orientation in the wine industry; and understand the role of research (and academics' social responsibility) for the diffusion of a sustainable orientation within the wine industry. The purpose of this paper is to provide a detailed overview of the main research contributions to the issue of sustainability in the wine industry.
Keywords: 330; Research trends; Sustainability; Systematic literature review